Back Cover: Nanomaterial‐mediated platinum drug‐based combinatorial cancer therapy (View 1/2021). Issue 1 (6th February 2021) - Deng, Zhiqin; Wang, Na; Ai, Fujin; Wang, Zhigang; Zhu, Guangyu
Abstract : In article number 20200030, Guangzhi Zhu, Zhigang Wang and their colleagues have displayed that nanomaterial‐mediated combinatorial therapy based on platinum drugs for improved anticancer efficacy.